2012
DOI: 10.1016/j.stem.2012.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Lineage Specification Roles for NANOG, OCT4, and SOX2 in Human Embryonic Stem Cells

Abstract: Nanog, Oct4, and Sox2 are the core regulators of mouse (m)ESC pluripotency. Although their basic importance in human (h)ESCs has been demonstrated, the mechanistic functions are not well defined. Here, we identify general and cell-line-specific requirements for NANOG, OCT4, and SOX2 in hESCs. We show that OCT4 regulates, and interacts with, the BMP4 pathway to specify four developmental fates. High levels of OCT4 enable self-renewal in the absence of BMP4 but specify mesendoderm in the presence of BMP4. Low le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

52
429
1
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 483 publications
(490 citation statements)
references
References 52 publications
52
429
1
8
Order By: Relevance
“…Interestingly, we found that although SOX2 depletion disrupted pluripotency and induced mesendoderm activities in hESCs, the upregulation of mesendoderm markers upon SOX2 depletion was much less rapid and drastic than enforced MSX2 expression (Supplementary information, Figure S7A). These results are consistent with an earlier study [54]. We therefore inferred that additional pathway(s) might mediate the function of MSX2 in mesendoderm induction.…”
Section: Nodal Signaling Is An Essential Downstream Effector Of Msx2supporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, we found that although SOX2 depletion disrupted pluripotency and induced mesendoderm activities in hESCs, the upregulation of mesendoderm markers upon SOX2 depletion was much less rapid and drastic than enforced MSX2 expression (Supplementary information, Figure S7A). These results are consistent with an earlier study [54]. We therefore inferred that additional pathway(s) might mediate the function of MSX2 in mesendoderm induction.…”
Section: Nodal Signaling Is An Essential Downstream Effector Of Msx2supporting
confidence: 93%
“…SOX2 is an integral component of the core transcriptional circuitry of pluripotency and also plays an essential role in neuroectoderm specification of hPSCs [52,53]. Depletion of SOX2 in hPSCs disrupts pluripotency and induces mesendoderm activities, reminiscent of MSX2 overexpression [54,55]. We thus asked whether SOX2 is a downstream target of MSX2 in mesendoderm differentiation.…”
Section: Msx2 Suppresses Sox2 Via Directly Binding To Sox2 Promotermentioning
confidence: 99%
“…First, we verified the compensation effect of SOX3 on SOX2 depletion reported by Wang et al [5] in two lines of hESCs, H9 [32] and SHhES2 [33] (si2/3-1 and si2/3-2) were used to KD SOX2 in hESCs and two sets of siRNA oligos targeting SOX2 (si2-1 and si2-2) were used in hNPCs. Analyses of RNA-seq data identified around 4 000 altered genes for each oligo set in Downregulated genes in both cell types were enriched in cell proliferation, an important aspect of self-renewal ( Figure 3A).…”
Section: Sox2 Safeguards Stemness and Directs Specific Developmental supporting
confidence: 76%
“…The role of SOX2 in human ESCs (hESCs) and human NPCs (hNPCs) is poorly defined; controversies remain regarding differentiated lineages after silencing SOX2 in hESCs [3,4]. Recently, Wang et al [5] reported that SOX2 knockdown (KD) caused a compensational increase in SOX3 expression and that simultaneous depletion of SOX2 and SOX3 led to primitive streak induction in hESCs. Also, SOX2 KD was reported to affect hNPCs proliferation and neurogenesis rather than apoptosis through a SOX2-Lin28/let7 pathway [6].…”
Section: Introductionmentioning
confidence: 99%
“…Abbreviations: BFA1, bafilomycin A1; hESC, human embryonic stem cell; UPS, ubiquitin-proteasome system. Cho, Han, Kim et al 433 www.StemCells.com V C AlphaMed Press 2013 of hESCs [13], suggesting that the degradation of excess proteins is essential to maintain the pluripotency of hESCs. Our results represented that autophagy and the UPS cooperate to regulate the levels of proteins upregulated after medium exchange ( Fig.…”
Section: Discussionmentioning
confidence: 99%